Impacts of Livestock Grazing on Wild Ungulate Habitat in the Khata Corridor, Bardiya, Nepal - Usha Dahal; Nirjala Raut; Anubhav Dhital; Suruchi Mainali; Deepak Gautam; Shankar Tripathi (International Journal of Forestry Research)
The wildlife population is an important part of the forest ecosystem and plays a crucial role in maintaining ecosystem health and integrity. In many grassland ecosystems, wild herbivores face substantial competition for space and resource use from livestock over grazing resources. Livestock and ungulates have shared a large portion of the Terai forest resources for decades, but little information has been explored about the influence of livestock on the grassland ecosystems of the protected areas of the Terai region of Nepal. We assessed the impact of livestock grazing on wild ungulate habitat in the Khata Corridor, Bardiya, Nepal. We used direct field observation, key informant interview (n = 10), focus group discussion (n = 5), and a questionnaire survey with local households to study the seasonal occurrence of wild ungulates in multiple habitats, livestock rearing practices, stocking density, and resource use by domestic livestock in and around the forest land of villages located in the Khata Corridor, Bardiya, Nepal. We followed livestock herds from the early morning to their return for consecutive days in each sample village to estimate the grazing circuits. We individually recorded a total number of grazing cattle in five different habitats while following the cattle grazing path by direct and indirect observation. Morisita’s index was used to evaluate the habitat overlap between domestic livestock and wild ungulates. The domestic cattle had a higher habitat overlap and effective stocking density in winter than wild ungulates in summer in the corridor forest. Lower availability of forage around the village led to the concerted effort of grazing in the forest, increasing the higher effective stocking density in winter, leading to the competition with wild ungulates. However, the carrying capacity is highly unevenly observed across the region, and overgrazing is found in many areas of the forest corridor. We recommend the development of comprehensive wildlife livestock grazing strategies for planning sustainable livestock farming and for important wildlife areas to maintain long-term landscape connectivity to protect migrating endangered wild species.